Outbreak of carbapenem-resistant Providencia rettgeri in a tertiary hospital - Lekalakala, M. R; Tshisevhe, V. S; Tshuma, N; van Rensburg, S Janse; Mbelle, N (SAMJ South African Medical Journal, 2018)
The emergence of resistance to multiple antimicrobial agents in pathogenic bacteria is a significant public health threat, as there are limited effective antimicrobial agents for infections caused by multidrug-resistant (MDR) bacteria. Several MDR bacteria are now frequently detected. Carbapenem resistance in Enterobacteriaceae is often plasmid mediated, necessitating stringent infection control practices. We describe an outbreak of carbapenem-resistant Providencia rettgeri involving 4 patients admitted to intensive care and high-care units at a tertiary hospital. Clinical and demographic characteristics of 4 patients with carbapenem-resistant P. rettgeri were documented. All P. rettgeri isolated in these cases had a carbapenem-resistant antibiogram, with resistance to imipenem, ertapenem and meropenem. These cases could be epidemiologically linked. A multiprong approach, simultaneously targeting antibiotic stewardship, universal precautions and appropriate transmission-based precaution practices, is integral to prevention and control of nosocomial infections
Article published in the SAMJ South African Medical Journal January 2017, Vol. 107, No. 1
Keywords: Outbreak; Carbapenem-resistant Providencia rettgeri; Tertiary hospital; Nosocomial infections; Anti-infectile agents